2014
DOI: 10.1371/journal.pone.0094944
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and High Fever Are Associated with Subacute Motor Deterioration in Parkinson Disease: A Nested Case-Control Study

Abstract: BackgroundIn Parkinson disease (PD), systemic inflammation caused by respiratory infections such as pneumonia frequently occurs, often resulting in delirium in the advanced stages of this disease. Delirium can lead to cognitive and functional decline, institutionalization, and mortality, especially in the elderly. Inflammation causes rapid worsening of PD motor symptoms and signs, sometimes irreversibly in some, but not all, patients.PurposeTo identify factors associated with subacute motor deterioration in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 26 publications
1
42
0
4
Order By: Relevance
“…27,28 Heart diseases such as angina and myocardial infraction, 33 respiratory diseases such as emphysema/asthma/COPD, 34 and stroke/brain hemorrhage 35 are known to be leading causes of death. Diabetes 25,36 and Parkinson’s disease 37,38 have been shown to be independently associated with functional deterioration and institutionalization. The effect of additional risk factors, including complete/partial paralysis 39 and mental/psychiatric disorder 40 on functional deterioration, institutionalization, and death may be mitigated by education or clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Heart diseases such as angina and myocardial infraction, 33 respiratory diseases such as emphysema/asthma/COPD, 34 and stroke/brain hemorrhage 35 are known to be leading causes of death. Diabetes 25,36 and Parkinson’s disease 37,38 have been shown to be independently associated with functional deterioration and institutionalization. The effect of additional risk factors, including complete/partial paralysis 39 and mental/psychiatric disorder 40 on functional deterioration, institutionalization, and death may be mitigated by education or clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is synthesized in the liver and is then transported to accumulate, or is synthesized in neurons, in neurodegenerative lesions in the brains of Alzheimer’s disease patients [ 8 ]. Recent evidence suggests that systemic inflammation contributes to the exacerbation of acute symptoms of chronic neurodegenerative disease [ 20 , 42 , 43 ], suggesting that systemic inflammation seems to promote neurodegeneration. Neuroinflammation can also elicit activation of inflammasome and caspase-1 in the brains of patients with Alzheimer disease [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of PD, systemic inflammatory stimuli can promote neuroinflammation by accelerating dopaminergic neurodegeneration in the substantia nigra [ 5 8 ]. Although we previously demonstrated that acute systemic inflammation can worsen PD motor symptoms [ 9 ], the association between chronic systemic inflammations and neurodegeneration in PD patients has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%